PEMANFAATAN HASIL PENELITIAN SITUS GUNUNG WINGKO - Alifah Alifah (Berkala Arkeologi, 2013)
Gunung Wingko is one of the Bronze Age sites located in Bantul Regency or approximately 25 km south from Yogyakarta city and 1.5 km from Indian Ocean coastline. This site became known in 1972, and since then an intensive research had been conducted there, surveys as well as excavations. Information related to the Gunung Wingko community life reconstruction has been obtained from the research. However, nowadays the site seemed to be forgotten within the contexts of historical reconstruction, in particular by the community of Yogyakarta and its nearby surrounding. The fast change of land use has caused damage to the site research has provided some culture information but in the other hand the management and utilization of the research results are still minimal. In this paper will be discussed how to utilize result in Gunung Wingko site based on conservation efforts. The Results of this paper are expected to be used as a reference to managing the site.